Participatory and Compassionate Communication Strategy in Empowering Persons with Disabilities at Rumah Kinasih Foundation Blitar - Gilang Aji; Galuh Gita Indrajayani; Anggun Herawati; Farah Nabila Rahmawati; Anis Azimah (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
To carry out empowerment for groups with disabilities, the communication process is the central point of achieving success.To do empowerment itself is not an easy thing, it takes a certain strategy or approach and a sustainable process, one of which is empowerment communication. Communication for empowering people with disabilities is an effective strategy to change the general public's view of people with disabilities who consider their limitations as incapable of being independent. This research try to find the communication strategy to empower persons with disabilities in Rumah Kinasih Foundation Blitar. This study uses a qualitative approach, case study method and data collection by means of interviews. The Result show that to empower the disabled people, communication should use participative, persuasive, and compassion way. Communication with them use more effort and carefulness. In Rumah Kinasih, they also use reward to make disabled people more productive.